2018
DOI: 10.1093/mnras/sty660
|View full text |Cite
|
Sign up to set email alerts
|

Flickering in AGB stars: probing the nature of accreting companions

Abstract: Binary companions to asymptotic giant branch (AGB) stars are an important aspect of their evolution. Few AGB companions have been detected, and in most cases it is difficult to distinguish between main-sequence and white dwarf companions. Detection of photometric flickering, a tracer of compact accretion disks around white dwarfs, can help identify the nature of these companions. In this work, we searched for flickering in four AGB stars suggested to have likely accreting companions. We found no signs for flic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…We note that much smaller-amplitude photometric variations have been recently reported at optical wavelengths (e.g., 0.06 mag peak-to-peak in the u ′ band with a typical timescale of 10 min) for Y Gem using ground-based differential photometry (Snaid et al 2018). Although a comparison with differential photometry of two field stars indicates that these variations are significant, the effects of aperture photometry in variable seeing conditions can produce spurious fluctuations that are not easily quantified.…”
Section: Results and Analysismentioning
confidence: 61%
See 1 more Smart Citation
“…We note that much smaller-amplitude photometric variations have been recently reported at optical wavelengths (e.g., 0.06 mag peak-to-peak in the u ′ band with a typical timescale of 10 min) for Y Gem using ground-based differential photometry (Snaid et al 2018). Although a comparison with differential photometry of two field stars indicates that these variations are significant, the effects of aperture photometry in variable seeing conditions can produce spurious fluctuations that are not easily quantified.…”
Section: Results and Analysismentioning
confidence: 61%
“…Assuming that the combined luminosity of the hot and cool blackbodies results from accretion, i.e., L acc = 13 L ⊙ during exposures 40–50, then taking L acc ≲ GṀ acc M c / R c , where Ṁ acc is the accretion rate, and M c ~ 0.35 M ⊙ and R c = 0.44 R ⊙ (as above), we find that Ṁ acc > 5×10 −7 M ⊙ yr −1 . This relatively large accretion rate makes wind-accretion mechanisms such as Bondi-Hoyle or wind Roche-lobe overflow (e.g., Chen et al 2017, Huarte-Espinosa et al 2013) unfeasible because Y Gem does not have a detectable wind – the very weak, narrow CO J=2–1 emission line detected towards it likely arises in an extended disk (Setal11); and the infrared-excess is negligible or very low (McDonald et al 2012) implying a mass-loss rate of ≲10 −7 M ⊙ yr −1 (Snaid et al 2018). Therefore, either the primary overflows its Roche lobe and transfers material to the accreting star, or accretion occurs within a common-envelope (CE) configuration.…”
Section: Discussionmentioning
confidence: 99%
“…In three out of four XMM-Newton observations (except in ObsID 0763050401), Y Gem shows L X /L UV < 0.1, and thus implies the existence of an accretion disk in Y Gem. The disk scenario is also supported by the photometric flickering in Y Gem (Snaid et al 2018).…”
Section: Estimating the System Properties Of Y Gemmentioning
confidence: 82%
“…For example, Sion et al (2002) found an outflow velocity of 170 km s −1 for RW Hydrae, which is a WD SySt. Moreover, the recent discovery of the photometric flickering in Y Gem also favors the existence of a WD companion (Snaid et al 2018). We then discuss if the accreting WD scenario can account for various observed properties of Y Gem as follows.…”
Section: Wd-syst Scenariomentioning
confidence: 99%
See 1 more Smart Citation